Hakluyt's promise: an Elizabethan's obsession for an English America - Mancall, Peter C. (Yale Univ. Press, 2007)
London, c.1592: Woodson's tusk. -- London, 1568: The visit. -- Oxford, c.1571: Rumors. -- Oxford, 1577: The ice. -- Oxford, c.1580: Passages. -- Paris, 1583: The devouring sea. -- Paris and London, 1584 to 1589: Cabinets and curiosities. -- London, 1590 to 1600: Truth and lies. -- London, 1609: Virginia richly valued. -- Wetheringsett and London, 1614: The Malayan dialogues